Molecular epidemiology Characterization of clinically important staphylococcus aureus - Elmnafi, Amghalia M.S. (2009)
Methicillin-resistant Staphylococcus aureus (MRSA), a hospital based infection has emerged as a cause of skin infections and invasive infections among healthy adults and children in the community. The present research successfully established molecular characteristics of clinical MRSA isolates to differentiate these strains from methicillin sensitive Staphylococcus aureus (MRSA) isolates. These relevant molecular characterictics of local MRSA contribute as initial database of these isolates in order to fully understand the epidemiology, microbiology and pathophysiology of these infections. A total of 90 isolates from different locations in Malaysia were included in the study. To investigate the epidemiology of S.aureus in Malaysia. Two highly reliable typing methods, randomly amplified polymorphic DNA and Rep-PCR were applied to 50 S.aureus hospital isolates showed consistent clonal groupings of isolates based on geographical locations. However, MRSA and MSSA strains are clustered together with no differentiation into separate groups or cluster. Further molecular differentiation of isolates was obtained through genotypic profiling 16S ribosomal RNA (rRNA) gene sequence. The clinical isolates were differentiated from the environmental isolates. An important finding of the research is the optimization of molecular methods for simple amplification of various genes useful in epidemiological-linked infection management. These genes include those involved in methicillin-resistant S.aureus. By using S.aureus strains to be tested as templates, various oligonucleotides primers amplified the 533-bp region of mecA, 310-bp region of the mecR1 penicillin binding domain gene, 318-bp region of the mecR1 transmembrane domain gene, and 481-bp region of the mecR1 gene. The presence of these genes was confirmed by nucleotide sequence analysis.